Biomass-derived activated carbon for energy storage applications - Altwala, Afnan (2022)
Activated carbon is a porous carbon material with a broad range of applications as adsorbents in liquid and gas treatment, as well as in catalytic applications. The need for activated carbons is continuing to expand, because environmental pollution is an increasingly serious issue. Activated carbons’ (ACs) specific properties are determined by the properties of the starting materials and the activation methods utilised. Practically, the principal sources of commercial ACs are coal, wood and coconut shells. Given their low cost, sustainability and ready availability, various agricultural and forest by-products have recently gained considerable attention as alternative feedstock for the production of ACs. Accordingly, a major goal of this thesis is to explore and discover the synthesis conditions for generating highly porous materials from starting materials with little to no value, for example waste biomass. We employed (sawdust, SD), date seed (Phoenix dactylifera) and CNL carbon (from accidental and uncontrolled burning of wood under fierce fire conditions of the first Carbon Neutral Laboratory, CNL, building at Nottingham) as feedstock, in order to prepare the activated carbon. The principal objectives are to identify and investigate synthesis conditions for producing highly porous activated carbon for sustainable energy applications.